SPIRITUAL AND EDUCATIONAL PRINCIPLES AND STRATEGIES FOR COMBATING EXTREMISM AND TERRORISM (Scientific journal of the Fergana State University, 2026)
This article analyzes the socio-psychological roots of extremism and terrorism, their threats to the stability of society, and the role of spiritual and educational factors in combating them. The article highlights the issues of effectively combating extremism and terrorism in the Republic of Uzbekistan by strengthening the spiritual immunity of youth, forming a healthy worldview, and promoting religious tolerance.